Deeply-curable zirconia-containing dental repair resin and preparation method thereof
By preparing dental restorative resins with zirconia-silica nanoclusters, the problems of insufficient light-curing depth and poor mechanical properties of zirconia fillers have been solved, achieving a dental restorative resin with deep curing and high mechanical properties, which is suitable for oral medical devices.
Patent Information
- Application Number
- CN202411469251.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-18
AI Technical Summary
Existing dental restorative resins, when using zirconia fillers, suffer from insufficient light-curing depth and poor mechanical properties, making it difficult to meet clinical needs.
Zirconia-silica nanoclusters were used as fillers and nanoparticle clusters were prepared by three-fluid spray drying technology. Combined with methacrylate organic matrix and photoinitiator, deep curing and high mechanical properties were achieved.
This technology enables deep curing of dental restorative resins, improves X-ray resistance and mechanical properties, and extends the service life of the restorations.
Smart Images

Figure CN119454477A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dental restoration materials, and in particular to a deeply curable zirconium oxide-containing dental restoration resin and a preparation method thereof. Background Art
[0002] Dental restorative resin is a commonly used treatment material for treating caries. It is mainly composed of acrylic ester as the matrix and inorganic fillers as the reinforcing component. It is suitable for making fixed-hole-shaped teeth after tooth decay, fixing the filling material on the teeth, and restoring the defects and functions of the teeth. When conducting oral examinations and diagnoses, doctors often need to use X-rays to observe the internal structure and repair status of the teeth. Therefore, the restorative resin needs to have X-ray radiopacity in order to distinguish the restorative material from the natural tooth tissue, judge the repair effect, determine the position and shape of the restorative material, and ensure the tightness and stability of the restoration and the tooth.
[0003] At present, heavy metal oxides (such as barium oxide, strontium oxide, zinc oxide, zirconium oxide, etc.) are usually added to the restoration materials to give the materials X-ray radiopacity. In terms of physical properties, compared with barium oxide and strontium oxide, zirconium oxide has higher strength (800~1000MPa) and hardness (Vickers hardness up to 1250 HV or more), making the material less likely to be damaged during use, reducing wear and tear, thereby extending the service life of the restoration. However, in terms of optical properties, the refractive index of zirconium oxide is above 2.0, which is much higher than the 1.42 of acrylate. Adding it to the resin as a filler often reduces the curing depth of the material. According to the data disclosed by the State Food and Drug Administration, the fillers used in the restorative resin products currently registered in China that have an X-ray blocking effect are all barium oxide or strontium oxide glass powder (such as the composite resin filling material of Gusha Dental Co., Ltd. (Registration No.: Guoxie No. 20163171314) uses barium aluminum glass powder and silicon dioxide, the light-curing resin of Jilin Province Dentech Dental Materials Co., Ltd. (Registration No.: Guoxie No. 20173174296) uses strontium glass powder and silicon powder, and the light-curing composite resin of Changchun Yisi Medical Equipment Co., Ltd. (Registration No.: Guoxie No. 20243170421)). Since the refractive index of these two is around 1.5, which is close to the refractive index of the resin matrix acrylate, it helps the material achieve a higher curing depth. However, due to the influence of the physical properties of the filler itself, the strength and hardness of barium oxide and strontium oxide are far inferior to zirconium oxide, so the existing resins have certain defects in mechanical properties.
[0004] At present, zirconium oxide is widely used in oral medical consumables as a high-strength material. The most common application is as a ceramic crown and CAD / CAM machinable material. For example, patent CN117598800B forms a crown composite material by mixing zirconium oxide and other ceramic materials, pressing and sintering; patent CN107903557B forms a ceramic blank by mixing different ceramic powders with acrylic resin in proportion, and then uses high temperature and high pressure to cure the acrylic resin matrix; these two methods are formed in the form of sintering melting or high-temperature curing, without considering the high refractive index of zirconium oxide, while dental restoration resins are usually formed in the form of light curing. Patent CN 117239197 A discloses a composite material of a zirconium oxide system, which uses a 3D printing method to reduce the thickness of each cured layer to 50μm, effectively solving the defect of low curing depth of zirconium oxide fillers. It is a good idea, but the 3D printing method is complicated to operate and is not suitable for clinical use of dental restoration resins.
[0005] Therefore, it is of great practical significance to develop a zirconia filling material that can be deeply cured and used for photocuring of dental restorations. Summary of the invention
[0006] Due to the above-mentioned defects in the prior art, the present invention provides a zirconia filling material that can be deeply cured and can be used for photocuring of dental restorations. The material takes zirconia as the main component and has a structure in the form of nanoparticle clusters. The zirconia-silicon oxide nanoparticle clusters are prepared by a special process, which solves the problem of poor transmittance of traditional zirconia fillers and can achieve deep curing of photocuring dental restoration resins. Due to the physical properties of the zirconia itself (high hardness and high strength) in its components, the dental restoration resin is endowed with higher mechanical properties, which effectively improves the service life of the restoration. At the same time, it has X-ray blocking properties, which facilitates doctors to accurately diagnose and guide treatment, so as to overcome the defect that current zirconia fillers cannot achieve a large curing depth and a good balance of photocuring molding.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a deeply curable zirconium oxide-containing dental restoration resin comprises the following steps:
[0009] (1) adding a silane coupling agent containing a double bond to a zirconium oxide dispersion, and performing a modification reaction under stirring to obtain a modified solution I; adding a silane coupling agent containing a double bond to a silicon dioxide dispersion, and performing a modification reaction under stirring to obtain a modified solution II;
[0010] (2) spray drying the modified solution I and the modified solution II through a three-fluid nozzle to obtain zirconium oxide silicon oxide nanoclusters, namely, ZrO2@SiO2 nanoclusters, wherein the three-fluid nozzle is provided with two dispersion liquid flow channels and the modified solution I and the modified solution II flow into the nozzle through the two dispersion liquid flow channels respectively, and the particle size distribution of the zirconium oxide silicon oxide nanoclusters is 0.05-500 μm;
[0011] (3) mixing and stirring the zirconium oxide and silicon oxide nanoclusters, the methacrylate organic matrix and the photoinitiator evenly;
[0012] (4) The mixture obtained in step (3) is subjected to light curing treatment to obtain a deeply curable zirconium oxide-containing dental restoration resin.
[0013] Modified solution I (zirconia dispersion modified by silane coupling agent containing double bonds) is fed through the inner flow channel of the three-fluid nozzle, and modified solution II (silicon dioxide dispersion modified by silane coupling agent containing double bonds) is fed through the outer flow channel of the three-fluid nozzle. When the two solutions flow through the nozzle of the nozzle and are sprayed out, they are respectively atomized by the gas and quickly form spherical clusters with a core-shell structure at high temperature. The zirconium oxide sprayed out from the inner flow channel constitutes the core of the cluster, and the silicon oxide sprayed out from the outer flow channel constitutes the shell of the cluster. The core composed of zirconium oxide occupies the center of the particle, which can play a good supporting role and provide high strength and hardness for the cluster; while the shell composed of silicon oxide can provide high light transmittance for the cluster due to the low refractive index of the substance itself and the gaps between the spherical particles.
[0014] The method for preparing the deeply curable zirconium oxide-containing dental restoration resin of the present invention comprises the following steps: using modified solution I (zirconium oxide dispersion modified by a silane coupling agent containing double bonds), modified solution II (silicon dioxide dispersion modified by a silane coupling agent containing double bonds) and a three-fluid nozzle to achieve higher strength and hardness of the resin while ensuring that the composite resin has X-ray radiopacity and effective curing depth, thereby extending the service life, breaking the industry's reliance on low-strength materials such as zinc oxide, barium oxide and strontium oxide, and solving the problem that zirconium oxide materials cannot be deeply cured due to their high refractive index, and having good application prospects.
[0015] As the preferred technical solution:
[0016] According to the method for preparing a deeply curable zirconium oxide-containing dental restoration resin as described above, the mass proportion of zirconium oxide silicon oxide nanoclusters in the deeply curable zirconium oxide-containing dental restoration resin is 40-85 wt.%.
[0017] According to the method for preparing a deeply curable dental restoration resin containing zirconium oxide, the size of the nanoparticles in the zirconium oxide dispersion and the silicon dioxide dispersion is 1-100 nm; the solid content in the zirconium oxide dispersion and the silicon dioxide dispersion is 5-40 wt.%;
[0018] The mass ratio of zirconium oxide in the zirconium oxide dispersion to silicon dioxide in the silicon dioxide dispersion is 1:100 to 100:1.
[0019] The particle size of zirconium oxide and silicon oxide dispersion is 1~100nm. If the particle size of nanoparticles is too large, the surface roughness of the composite resin will be too large, the polishing property will be poor, and the aesthetics of the restoration will be affected. Secondly, when the particle size is too large, the packing density of the filler will be too large, and light cannot penetrate, which will reduce the curing depth of the resin. If the particle size of nanoparticles is too small, it will be difficult to disperse evenly in the matrix, and agglomerates may form, which will form stress concentration points, which will easily cause the composite resin to be destroyed when subjected to force, thereby reducing the mechanical strength of the resin. Secondly, if the particle size is too small, the interface bonding with the matrix will be weakened, resulting in poor interface bonding, which will affect the overall mechanical properties of the material. In summary, the particle size of 1-100nm is the best range for particles to take into account various performances.
[0020] The solid content in the dispersion is 5~40 wt.%, which is a parameter selected based on the processing technology of the spray dryer equipment. If the solid content is too low, the processing efficiency is too low, and the obtained particles may have high humidity, affecting the subsequent dispersion; if the solid content is too high, the overall viscosity of the dispersion will be high, causing the nozzle or other flow channels to be blocked.
[0021] The method for preparing a deeply curable zirconium oxide-containing dental restorative resin as described above, wherein in step (1), the uniform mixing temperature is 20-25°C and the mixing time is 1-3 hours;
[0022] The double bond-containing silane coupling agent is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane or γ-mercaptopropyltrimethoxysilane, and the mass ratio of the inorganic nanoparticles to the double bond-containing silane coupling agent is 100:1-50;
[0023] The reaction temperature of the modification reaction is 40-80°C and the reaction time is 1-24 h.
[0024] The method for preparing a deeply curable zirconium oxide-containing dental restoration resin as described above, wherein the two dispersion flow channels of the three-fluid nozzle are a middle flow channel, the fluid passing through which is a zirconium oxide dispersion, and an outer flow channel, the fluid passing through which is a silicon dioxide dispersion;
[0025] The spray drying conditions are as follows: the nozzle diameter is 0.5-2.0 μm, the spray flow rate of compressed air is 0.18-0.91 m 3 / min, the flow rate of the dispersion is 2.5~26.4 mL / min, and the drying temperature is 100~230℃.
[0026] If the nozzle diameter is too small, or even smaller than the particle size, the nozzle will be clogged; if the nozzle diameter is too large, the flow rate is too large, and the powder will be wet if the drying is not timely. If the spray flow rate is too small, the liquid cannot be atomized, and the liquid will drip in the form of droplets, and clustered powders cannot be obtained; if the spray flow rate is too large, the atomization surface will also become larger, causing the particles to be sprayed on the wall of the drying barrel and cannot be recovered, affecting the yield. If the flow rate is too small, the spray efficiency will be affected and it is not suitable for actual processing scenarios; if the flow rate is too large, the atomization effect will be poor, the powder loss will be large or the powder will be wet. The drying temperature is set according to the boiling point of the dispersion. Generally, the drying temperature is about 20°C higher than the boiling point of the dispersion. For example, if the dispersion is water dispersion, the boiling point of water is 100°C, and the drying temperature is generally set to 120°C. The above parameters will affect the effect of spray drying and need to be dynamically adjusted according to the actual working conditions.
[0027] In the method for preparing a deeply curable zirconium oxide-containing dental restorative resin as described above, in step (3), the methacrylate organic matrix is a mixture of bisphenol-A-dimethacrylate glycidyl ester and triethylene glycol dimethacrylate, and the mass ratio of bisphenol-A-dimethacrylate glycidyl ester to triethylene glycol dimethacrylate is 5-7:3-5;
[0028] The photoinitiator is selected from one or more of 4-N,N-dimethylaminobenzoic acid ethyl ester (4-EDMAB), 4-(dimethylamino)benzoic acid ethyl ester (DMABEE), N,N-dimethylamino ethyl methacrylate (DMAEMA), 2-ethyl dimethyl benzoate (EDB), N,N-dimethyl p-toluidine (DMPT), N-phenylglycine (NPG), diphenylphosphine oxide (TPO), 1-phenyl-1,2-propanedione (PPD), diphenyliodonium hexafluorophosphate (DFIHFP), camphorquinone (CPQ) and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (Irgacure 819), and the amount of the photoinitiator is 0.1-5 wt.% of the methacrylate organic matrix;
[0029] The mixing and stirring is carried out by using a rotating and revolving mixer and a three-roll mill;
[0030] The rotation speed of the rotary mixer is 600-3000 rpm, and the processing time is 3-10 min;
[0031] The three-roll mill has an inlet roller spacing of 10-100 μm, an outlet roller spacing of 5-50 μm, and a rotation speed of 10-100 rpm.
[0032] In the method for preparing a deeply curable zirconium oxide-containing dental restoration resin as described above, in step (4), the light curing is blue light curing, the wavelength of the blue light is 430-490 nm, and the power is 1200 mW / cm 2 The light curing time is 20~180 s.
[0033] In addition, the present invention also provides a deeply curable zirconium oxide-containing dental restoration resin, which is prepared by the preparation method described above.
[0034] As the preferred technical solution:
[0035] The deeply curable zirconia-containing dental restoration resin as described above has an X-ray blocking index of 1mm~3mm (equivalent aluminum plate thickness), a hardness of 50~90HV, and a curing depth of 1.8mm~3.0mm.
[0036] The deeply curable zirconia-containing dental restoration resin as described above has a flexural strength of 110-180 MPa, a flexural modulus of 10-20 GPa, and a compressive strength of 400-450 MPa.
[0037] The above technical solution is only a feasible technical solution of the present invention, and the protection scope of the present invention is not limited thereto. Those skilled in the art can reasonably adjust the specific design according to actual needs.
[0038] The above invention has the following advantages or beneficial effects:
[0039] (1) The preparation method of the present invention, by combining modified solution I (zirconia dispersion modified by a silane coupling agent containing double bonds), modified solution II (silicon dioxide dispersion modified by a silane coupling agent containing double bonds) with a three-fluid nozzle, ensures that the composite resin has X-ray radiopacity and effective curing depth, thereby achieving higher strength and hardness of the resin and extending the service life, breaking the industry's reliance on low-strength materials such as zinc oxide, barium oxide, and strontium oxide, and solving the problem that zirconium oxide materials cannot be deeply cured due to their high refractive index;
[0040] (2) The deeply curable zirconium oxide-containing dental restoration resin prepared by the present invention can be applied to the field of oral medical devices. It has good X-ray blocking performance, good mechanical properties (showing higher hardness, bending strength, bending modulus and compression strength than commercially available composite resins) and can be deeply cured. It can effectively improve the clinical effect of caries repair and extend the service life of the restoration, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The present invention and its features, appearance and advantages will become more apparent by reading the detailed description of non-limiting embodiments with reference to the following drawings. The same reference numerals indicate the same parts in all the drawings. The drawings are not drawn to scale, and emphasis is placed on illustrating the subject matter of the present invention.
[0042] Figure 1 is a schematic diagram of a three-fluid nozzle;
[0043] Figure 2 This is a scanning electron microscope image (micrometer scale) of the zirconium oxide silicon oxide nanoclusters prepared in Example 1;
[0044] Figure 3 This is a scanning electron microscope image (nanoscale) of the zirconium oxide silicon oxide nanoclusters prepared in Example 1;
[0045] Among them, 1-zirconium oxide dispersion flow channel, 2-silicon dioxide dispersion flow channel, 3-cluster outlet, 4-atomizing gas, 5-coolant outlet, 6-coolant inlet. DETAILED DESCRIPTION
[0046] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.
[0047] Example 1
[0048] A method for preparing a deeply curable zirconium oxide-containing dental restorative resin, the raw materials used are as follows: silicon dioxide dispersion (size: 16 nm, solid content: 40 wt.%), zirconium oxide dispersion (size: 13 nm, solid content: 40 wt.%), γ-aminopropyltrimethoxysilane, bisphenol-A-dimethylglycidyl dimethacrylate, triethylene glycol dimethacrylate, camphorquinone, 4-N, N-dimethylaminobenzoic acid ethyl ester.
[0049] The specific implementation steps are as follows:
[0050] Preparation of cluster powder: Add 10g of γ-aminopropyltrimethoxysilane to 150g of silica dispersion aqueous solution, heat to 80°C, and stir mechanically for 20 h to obtain silanized silica dispersion. Take another 10g of γ-aminopropyltrimethoxysilane and add it to 308g of zirconium oxide dispersion aqueous solution, heat to 80°C, and stir mechanically for 20 h to obtain silanized zirconium oxide dispersion. Use a peristaltic pump to pump the dispersion into a three-fluid nozzle with a diameter of 1.0 mm (such as Figure 1 As shown in the figure, the middle channel flows into the zirconium oxide dispersion with a flow rate of 5 ml / min, and the outer channel flows into the silicon dioxide dispersion with a flow rate of 5 ml / min. The flow rate is 0.91 m 3 / min compressed air atomization, the drying temperature is 135℃, and it is recorded as ZrO2@SiO2 clusters.
[0051] Preparation of resin matrix: The organic monomer is a mixture of bisphenol-A-dimethacrylate glycidyl ester and triethylene glycol dimethacrylate in a mass ratio of 6:4; the photoinitiator is a mixture of camphorquinone and 4-N, N-dimethylaminobenzoic acid ethyl ester in a mass ratio of 1:4; the amount of the photoinitiator used is 1.4 wt.% of the organic monomer.
[0052] Preparation of dental restoration resin: ZrO2@SiO2 clusters were mixed into the resin matrix as inorganic fillers, with a mass ratio of powder to resin matrix of 7:3. The mixture was premixed in a rotary mixer at 500 rpm for 3 min, and then placed in a three-roll mill with an inlet roller spacing of 100 μm, an outlet roller spacing of 50 μm, and a rotation speed of 80 rpm for uniform mixing. The mixture was then illuminated with an LED lamp (wavelength of 460 nm, power of 1200 mW / cm 2 ) and cured for 180 s to obtain a deeply curable zirconium oxide-containing dental restorative resin.
[0053] The prepared deep curable zirconia-containing dental restoration resin has an X-ray opacity of 1.5 mm (equivalent aluminum plate thickness), a hardness of 80 HV, a curing depth of 2.5 mm, a bending strength of 125 MPa, a bending modulus of 12 GPa, and a compressive strength of 400 MPa.
[0054] Example 2
[0055] A method for preparing a deeply curable zirconium oxide-containing dental restoration resin, the raw materials used are as follows: silicon dioxide dispersion (size: 16 nm, solid content: 40 wt.%), zirconium oxide dispersion (size: 13 nm, solid content: 40 wt.%), γ-aminopropyltrimethoxysilane, bisphenol-A-dimethacrylate glycidyl ester, triethylene glycol dimethacrylate, camphorquinone, 4-N, N-dimethylaminobenzoic acid ethyl ester. The sizes of silicon dioxide and zirconium oxide can be set according to needs, such as 1, 20, 50, 70, 100 nm.
[0056] The specific implementation steps are as follows:
[0057] Preparation of cluster powder: Add 10g of γ-aminopropyltrimethoxysilane to 150g of silica dispersion aqueous solution, heat to 80°C, and stir mechanically for 20 hours to obtain a silanized silica dispersion. Take another 10g of γ-aminopropyltrimethoxysilane and add it to 308g of zirconium oxide dispersion aqueous solution, heat to 80°C, and stir mechanically for 20 hours to obtain a silanized zirconium oxide dispersion. Use a peristaltic pump to pump the dispersion into a three-fluid nozzle with a diameter of 1.0 mm. The middle flow channel enters the zirconium oxide dispersion with a flow rate set to 15ml / min, and the outer flow channel enters the silica dispersion with a flow rate set to 5ml / min. The flow rate is 0.91 m 3 / min compressed air atomization, the drying temperature is 135℃, and it is recorded as ZrO2@SiO2 clusters.
[0058] Preparation of resin matrix: The organic monomer is a mixture of bisphenol-A-dimethacrylate glycidyl ester and triethylene glycol dimethacrylate in a mass ratio of 6:4; the photoinitiator is a mixture of camphorquinone and 4-N, N-dimethylaminobenzoic acid ethyl ester in a mass ratio of 1:4; the amount of the photoinitiator used is 1.4 wt.% of the organic monomer.
[0059] Preparation of dental restoration resin: ZrO2@SiO2 clusters were mixed into the resin matrix as inorganic fillers, with a mass ratio of powder to resin matrix of 7:3. The mixture was premixed in a rotary mixer at 500 rpm for 3 min, and then placed in a three-roll mill with an inlet roller spacing of 100 μm, an outlet roller spacing of 50 μm, and a rotation speed of 80 rpm for uniform mixing. The mixture was then illuminated with an LED lamp (wavelength of 460 nm, power of 1200 mW / cm 2 ) and cured for 180 s to obtain a deeply curable zirconium oxide-containing dental restorative resin.
[0060] The prepared deep curable zirconia-containing dental restoration resin has an X-ray shielding rate of 2 mm (equivalent aluminum plate thickness), a hardness of 82 HV, a curing depth of 2.2 mm, a bending strength of 135 MPa, a bending modulus of 12 GPa, and a compressive strength of 400 MPa.
[0061] Example 3
[0062] A method for preparing a deeply curable zirconium oxide-containing dental restorative resin, the raw materials used are as follows: silicon dioxide dispersion (size: 16 nm, solid content: 40 wt.%), zirconium oxide dispersion (size: 13 nm, solid content: 40 wt.%), γ-aminopropyltrimethoxysilane, bisphenol-A-dimethylglycidyl dimethacrylate, triethylene glycol dimethacrylate, camphorquinone, 4-N, N-dimethylaminobenzoic acid ethyl ester.
[0063] The specific implementation steps are as follows:
[0064] Preparation of cluster powder: Add 10g of γ-aminopropyltrimethoxysilane to 150g of silica dispersion aqueous solution, heat to 80°C, and stir mechanically for 20 hours to obtain a silanized silica dispersion. Take another 10g of γ-aminopropyltrimethoxysilane and add it to 308g of zirconium oxide dispersion aqueous solution, heat to 80°C, and stir mechanically for 20 hours to obtain a silanized zirconium oxide dispersion. Use a peristaltic pump to pump the dispersion into a three-fluid nozzle with a diameter of 1.0 mm. The middle flow channel enters the zirconium oxide dispersion with a flow rate set to 5ml / min, and the outer flow channel enters the silica dispersion with a flow rate set to 15ml / min. The flow rate is 0.91 m 3 / min compressed air atomization, the drying temperature is 135℃, and it is recorded as ZrO2@SiO2 clusters.
[0065] Preparation of resin matrix: The organic monomer is a mixture of bisphenol-A-dimethacrylate glycidyl ester and triethylene glycol dimethacrylate in a mass ratio of 6:4; the photoinitiator is a mixture of camphorquinone and 4-N, N-dimethylaminobenzoic acid ethyl ester in a mass ratio of 1:4; the amount of the photoinitiator used is 1.4 wt.% of the organic monomer.
[0066] Preparation of dental restoration resin: ZrO2@SiO2 clusters were mixed into the resin matrix as inorganic fillers, with a mass ratio of powder to resin matrix of 7:3. The mixture was premixed in a rotary mixer at 500 rpm for 3 min, and then placed in a three-roll mill with an inlet roller spacing of 100 μm, an outlet roller spacing of 50 μm, and a rotation speed of 80 rpm for uniform mixing. The mixture was then illuminated with an LED lamp (wavelength of 460 nm, power of 1200 mW / cm 2) and cured for 180 s to obtain a deeply curable zirconium oxide-containing dental restorative resin.
[0067] The prepared deep curable zirconia-containing dental restoration resin has an X-ray opacity of 1.32 mm (equivalent aluminum plate thickness), a hardness of 72 HV, a curing depth of 2.65 mm, a bending strength of 120 MPa, a bending modulus of 12 GPa, and a compressive strength of 400 MPa.
[0068] Example 4
[0069] A method for preparing a deeply curable zirconium oxide-containing dental restorative resin, the raw materials used are as follows: silicon dioxide dispersion (size: 16 nm, solid content: 40 wt.%), zirconium oxide dispersion (size: 13 nm, solid content: 40 wt.%), γ-aminopropyltrimethoxysilane, bisphenol-A-dimethylglycidyl dimethacrylate, triethylene glycol dimethacrylate, camphorquinone, 4-N, N-dimethylaminobenzoic acid ethyl ester.
[0070] The specific implementation steps are as follows:
[0071] Preparation of cluster powder: Add 10g of γ-aminopropyltrimethoxysilane to 150g of silica dispersion aqueous solution, heat to 80°C, and stir mechanically for 20 hours to obtain a silanized silica dispersion. Take another 10g of γ-aminopropyltrimethoxysilane and add it to 308g of zirconium oxide dispersion aqueous solution, heat to 80°C, and stir mechanically for 20 hours to obtain a silanized zirconium oxide dispersion. Use a peristaltic pump to pump the dispersion into a three-fluid nozzle with a diameter of 1.0 mm. The middle flow channel enters the zirconium oxide dispersion with a flow rate set to 25ml / min, and the outer flow channel enters the silica dispersion with a flow rate set to 5ml / min. The flow rate is 0.91 m 3 / min compressed air atomization, the drying temperature is 135℃, and it is recorded as ZrO2@SiO2 clusters.
[0072] Preparation of resin matrix: The organic monomer is a mixture of bisphenol-A-dimethacrylate glycidyl ester and triethylene glycol dimethacrylate in a mass ratio of 6:4; the photoinitiator is a mixture of camphorquinone and 4-N, N-dimethylaminobenzoic acid ethyl ester in a mass ratio of 1:4; the amount of the photoinitiator used is 1.4 wt.% of the organic monomer.
[0073] Preparation of dental restoration resin: ZrO2@SiO2 clusters were mixed into the resin matrix as inorganic fillers, with a mass ratio of powder to resin matrix of 7:3. The mixture was premixed in a rotary mixer at 500 rpm for 3 min, and then placed in a three-roll mill with an inlet roller spacing of 100 μm, an outlet roller spacing of 50 μm, and a rotation speed of 80 rpm for uniform mixing. The mixture was then illuminated with an LED lamp (wavelength of 460 nm, power of 1200 mW / cm 2 ) and cured for 180 s to obtain a deeply curable zirconium oxide-containing dental restorative resin.
[0074] The prepared deep curable zirconia-containing dental restoration resin has an X-ray shielding rate of 2.15 mm (equivalent aluminum plate thickness), a hardness of 85 HV, a curing depth of 2 mm, a bending strength of 137 MPa, a bending modulus of 12 GPa, and a compressive strength of 400 MPa.
[0075] Example 5
[0076] A method for preparing a deeply curable zirconium oxide-containing dental restorative resin, the raw materials used are as follows: silicon dioxide dispersion (size: 16 nm, solid content: 40 wt.%), zirconium oxide dispersion (size: 13 nm, solid content: 40 wt.%), γ-aminopropyltrimethoxysilane, bisphenol-A-dimethylglycidyl dimethacrylate, triethylene glycol dimethacrylate, camphorquinone, 4-N, N-dimethylaminobenzoic acid ethyl ester.
[0077] The specific implementation steps are as follows:
[0078] Preparation of cluster powder: Add 10g of γ-aminopropyltrimethoxysilane to 150g of silica dispersion aqueous solution, heat to 80°C, and stir mechanically for 20 hours to obtain a silanized silica dispersion. Take another 10g of γ-aminopropyltrimethoxysilane and add it to 308g of zirconium oxide dispersion aqueous solution, heat to 80°C, and stir mechanically for 20 hours to obtain a silanized zirconium oxide dispersion. Use a peristaltic pump to pump the dispersion into a three-fluid nozzle with a diameter of 1.0 mm. The middle flow channel enters the zirconium oxide dispersion with a flow rate set to 5ml / min, and the outer flow channel enters the silica dispersion with a flow rate set to 25ml / min. The flow rate is 0.91 m 3 / min compressed air atomization, the drying temperature is 135℃, and it is recorded as ZrO2@SiO2 clusters.
[0079] Preparation of resin matrix: The organic monomer is a mixture of bisphenol-A-dimethacrylate glycidyl ester and triethylene glycol dimethacrylate in a mass ratio of 6:4; the photoinitiator is a mixture of camphorquinone and 4-N, N-dimethylaminobenzoic acid ethyl ester in a mass ratio of 1:4; the amount of the photoinitiator used is 1.4 wt.% of the organic monomer.
[0080] Preparation of dental restoration resin: ZrO2@SiO2 clusters were mixed into the resin matrix as inorganic fillers, with a mass ratio of powder to resin matrix of 7:3. The mixture was premixed in a rotary mixer at 500 rpm for 3 min, and then placed in a three-roll mill with an inlet roller spacing of 100 μm, an outlet roller spacing of 50 μm, and a rotation speed of 80 rpm for uniform mixing. The mixture was then illuminated with an LED lamp (wavelength of 460 nm, power of 1200 mW / cm 2 ) and cured for 180 s to obtain a deeply curable zirconium oxide-containing dental restorative resin.
[0081] The prepared deep curable zirconia-containing dental restoration resin has an X-ray shielding rate of 1.12 mm (equivalent aluminum plate thickness), a hardness of 68 HV, a curing depth of 2.7 mm, a bending strength of 121 MPa, a bending modulus of 12 GPa, and a compressive strength of 400 MPa.
[0082] Comparative Example 1
[0083] A method for preparing a dental restorative resin, the raw materials used are as follows: silicon dioxide dispersion (size: 16 nm, solid content: 40 wt.%), zirconium oxide dispersion (size: 13 nm, solid content: 40 wt.%), γ-aminopropyltrimethoxysilane, bisphenol-A-dimethylglycidyl methacrylate, triethylene glycol dimethacrylate, camphorquinone, 4-N,N-dimethylaminobenzoic acid ethyl ester.
[0084] The specific implementation steps are as follows:
[0085] Preparation of cluster powder: 150g of silica dispersion and 308g of zirconium oxide dispersion were stirred and mixed evenly, 20g of γ-aminopropyltrimethoxysilane was added to the mixed solution, the temperature was raised to 80°C, and mechanical stirring was continued for 20 h to obtain silanized zirconium oxide silica dispersion. The modified mixed dispersion was pumped into a two-fluid nozzle with a diameter of 1.0mm using a peristaltic pump, and the flow rate was set to 10ml / min. The flow rate was 0.91 m 3 / min compressed air atomization, the drying temperature is 135℃, and it is recorded as ZrO2@SiO2 clusters.
[0086] Preparation of resin matrix: The organic monomer is a mixture of bisphenol-A-dimethacrylate glycidyl ester and triethylene glycol dimethacrylate in a mass ratio of 6:4; the photoinitiator is a mixture of camphorquinone and 4-N, N-dimethylaminobenzoic acid ethyl ester in a mass ratio of 1:4; the amount of the photoinitiator used is 1.4 wt.% of the organic monomer.
[0087] Preparation of dental restoration resin: ZrO2@SiO2 clusters were mixed into the resin matrix as inorganic fillers, with a mass ratio of powder to resin matrix of 7:3. The mixture was premixed in a rotary mixer at 500 rpm for 3 min, and then placed in a three-roll mill with an inlet roller spacing of 100 μm, an outlet roller spacing of 50 μm, and a rotation speed of 80 rpm for uniform mixing. The mixture was then illuminated with an LED lamp (wavelength of 460 nm, power of 1200 mW / cm 2 ) and cured for 180 s to obtain dental restorative resin.
[0088] The prepared dental restoration resin has an X-ray obstruction rate of 1.5 mm (equivalent aluminum plate thickness), a hardness of 82 HV, a curing depth of 1.7 mm, a bending strength of 125 MPa, a bending modulus of 12 GPa, and a compressive strength of 400 MPa.
[0089] Comparative Example 2
[0090] A method for preparing a dental restorative resin, the raw materials used are as follows: silicon dioxide dispersion (size: 16 nm, solid content: 40 wt.%), γ-aminopropyltrimethoxysilane, bisphenol-A-dimethylglycidyl methacrylate, triethylene glycol dimethacrylate, camphorquinone, and ethyl 4-N,N-dimethylaminobenzoate.
[0091] The specific implementation steps are as follows:
[0092] Preparation of cluster powder: Add 20g of γ-aminopropyltrimethoxysilane to 300g of silica dispersion solution, heat to 80℃, and stir mechanically for 20h to obtain silanized silica dispersion, which is then divided into two equal parts, each of which is about 160g. Use a peristaltic pump to pump the two groups of liquid into a three-fluid nozzle with a diameter of 1.0 mm, and set the flow rate of the inner and outer flow channels to 5ml / min. The flow rate is 0.91 m 3 / min compressed air atomization, drying temperature is 135℃, recorded as SiO2 clusters.
[0093] Preparation of resin matrix: The organic monomer is a mixture of bisphenol-A-dimethacrylate glycidyl ester and triethylene glycol dimethacrylate in a mass ratio of 6:4; the photoinitiator is a mixture of camphorquinone and 4-N, N-dimethylaminobenzoic acid ethyl ester in a mass ratio of 1:4; the amount of the photoinitiator used is 1.4 wt.% of the organic monomer.
[0094] Preparation of dental restoration resin: SiO2 clusters were mixed as inorganic fillers into the resin matrix at a mass ratio of 7:3. The mixture was premixed in a rotary mixer at 500 rpm for 3 min. The mixture was placed in a three-roll mill with an inlet roller spacing of 100 μm, an outlet roller spacing of 50 μm, and a rotation speed of 80 rpm for uniform mixing. The mixture was illuminated by an LED lamp (wavelength of 460 nm, power of 1200 mW / cm 2 ) and cured for 180 s to obtain a composite resin for dental restoration.
[0095] The prepared composite resin for dental restoration has an X-ray shielding rate of 0.2 mm (equivalent aluminum plate thickness), a hardness of 58 HV, a curing depth of 2.85 mm, a bending strength of 105 MPa, a bending modulus of 12 GPa, and a compressive strength of 400 MPa.
[0096] By comparing the performance of the product obtained in Example 1 with that obtained in Comparative Example 1, it can be found that the presence of the three-fluid nozzle significantly improves the curing depth of the resin; by comparing the performance of the product obtained in Example 1 with that obtained in Comparative Example 2, it can be found that the addition of the zirconium oxide dispersion is crucial to the influence on the X-ray blocking performance, hardness and bending strength of the resin. Based on the above analysis, it can be seen that only through the organic combination of the three-fluid nozzle with the silicon dioxide dispersion and the zirconium oxide dispersion can the curing depth, X-ray blocking rate, hardness and mechanical properties of the resin be well balanced.
[0097] Comparative Example 3
[0098] A method for preparing a dental restorative resin, the raw materials used are as follows: silicon dioxide dispersion (size: 16 nm, solid content: 40 wt.%), barium oxide dispersion (size: 13 nm, solid content: 40 wt.%), γ-aminopropyltrimethoxysilane, bisphenol-A-dimethylglycidyl methacrylate, triethylene glycol dimethacrylate, camphorquinone, 4-N,N-dimethylaminobenzoic acid ethyl ester.
[0099] The specific implementation steps are as follows:
[0100] Preparation of cluster powder: Add 10g of γ-aminopropyltrimethoxysilane to 150g of silica dispersion aqueous solution, heat to 80°C, and stir mechanically for 20 hours to obtain silanized silica dispersion. Take another 10g of γ-aminopropyltrimethoxysilane and add it to 383g of barium oxide dispersion aqueous solution, heat to 80°C, and stir mechanically for 20 hours to obtain silanized barium oxide dispersion. Use a peristaltic pump to pump the dispersion into a three-fluid nozzle with a diameter of 1.0 mm. The middle flow channel enters the barium oxide dispersion with a flow rate set to 5ml / min, and the outer flow channel enters the silica dispersion with a flow rate set to 5ml / min. The flow rate is 0.91 m 3 / min compressed air atomization, the drying temperature is 135℃, and it is recorded as BaO@SiO2 clusters.
[0101] Preparation of resin matrix: The organic monomer is a mixture of bisphenol-A-dimethacrylate glycidyl ester and triethylene glycol dimethacrylate in a mass ratio of 6:4; the photoinitiator is a mixture of camphorquinone and 4-N, N-dimethylaminobenzoic acid ethyl ester in a mass ratio of 1:4; the amount of the photoinitiator used is 1.4 wt.% of the organic monomer.
[0102] Preparation of dental restoration resin: BaO@SiO2 clusters were mixed uniformly into the resin matrix as inorganic fillers, with a mass ratio of powder to resin matrix of 7:3. The mixture was premixed in a rotary mixer at 500 rpm for 3 min, and then placed in a three-roll mill with an inlet roller spacing of 100 μm, an outlet roller spacing of 50 μm, and a rotation speed of 80 rpm for uniform mixing. The mixture was then illuminated with an LED light (wavelength of 460 nm, power of 1200 mW / cm 2 ) and cured for 180 s to obtain a composite resin for dental restoration.
[0103] The prepared composite resin for dental restoration has an X-ray obstruction of 1.4 mm (equivalent aluminum plate thickness), a hardness of 68 HV, a curing depth of 2.5 mm, a bending strength of 115 MPa, a bending modulus of 12 GPa, and a compressive strength of 400 MPa.
[0104] Comparative Example 4
[0105] A method for preparing a dental restorative resin, the raw materials used are as follows: silicon dioxide dispersion (size: 16 nm, solid content: 40 wt.%), strontium oxide dispersion (size: 13 nm, solid content: 40 wt.%), γ-aminopropyltrimethoxysilane, bisphenol-A-dimethylglycidyl methacrylate, triethylene glycol dimethacrylate, camphorquinone, 4-N,N-dimethylaminobenzoic acid ethyl ester.
[0106] The specific implementation steps are as follows:
[0107] Preparation of cluster powder: Add 10g of γ-aminopropyltrimethoxysilane to 150g of silica dispersion in water, heat to 80°C, and stir mechanically for 20 hours to obtain a silanized silica dispersion. Take another 10g of γ-aminopropyltrimethoxysilane and add it to 259g of strontium oxide dispersion in water, heat to 80°C, and stir mechanically for 20 hours to obtain a silanized strontium oxide dispersion. Use a peristaltic pump to pump the dispersion into a three-fluid nozzle with a diameter of 1.0 mm. The middle flow channel enters the strontium oxide dispersion with a flow rate of 5ml / min, and the outer flow channel enters the silica dispersion with a flow rate of 5ml / min. The flow rate is 0.91 m 3 / min compressed air atomization, the drying temperature is 135℃, and it is recorded as SrO@SiO2 clusters.
[0108] Preparation of resin matrix: The organic monomer is a mixture of bisphenol-A-dimethacrylate glycidyl ester and triethylene glycol dimethacrylate in a mass ratio of 6:4; the photoinitiator is a mixture of camphorquinone and 4-N, N-dimethylaminobenzoic acid ethyl ester in a mass ratio of 1:4; the amount of the photoinitiator used is 1.4 wt.% of the organic monomer.
[0109] Preparation of dental restoration resin: SrO@SiO2 clusters were mixed uniformly into the resin matrix as inorganic fillers, with a mass ratio of powder to resin matrix of 7:3. The mixture was premixed in a rotary mixer at 500 rpm for 3 min, and then placed in a three-roll mill with an inlet roller spacing of 100 μm, an outlet roller spacing of 50 μm, and a rotation speed of 80 rpm for uniform mixing. The mixture was then illuminated with an LED light (wavelength of 460 nm, power of 1200 mW / cm 2 ) and cured for 180 s to obtain a composite resin for dental restoration.
[0110] The prepared composite resin for dental restoration has an X-ray shielding rate of 1.4 mm (equivalent aluminum plate thickness), a hardness of 72 HV, a curing depth of 2.3 mm, a bending strength of 118 MPa, a bending modulus of 12 GPa, and a compressive strength of 400 MPa.
[0111] Those skilled in the art should understand that those skilled in the art can implement variations by combining the prior art and the above embodiments, which will not be described in detail here. Such variations do not affect the essential content of the present invention, and will not be described in detail here.
[0112] The above describes the preferred embodiments of the present invention. It should be understood that the present invention is not limited to the above-mentioned specific embodiments, and the devices and structures that are not described in detail should be understood to be implemented in a common manner in the art; any technician familiar with the art can use the above-disclosed methods and technical contents to make many possible changes and modifications to the technical solutions of the present invention without departing from the scope of the technical solutions of the present invention, or modify them into equivalent embodiments of equivalent changes, which does not affect the essential content of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solutions of the present invention are still within the scope of protection of the technical solutions of the present invention.
Claims
1. A method for preparing a deeply curable zirconium oxide-containing dental restoration resin, characterized in that: The following steps are involved: (1) adding a silane coupling agent containing a double bond to a zirconium oxide dispersion, and performing a modification reaction under stirring to obtain a modified solution I; adding a silane coupling agent containing a double bond to a silicon dioxide dispersion, and performing a modification reaction under stirring to obtain a modified solution II; (2) spray drying the modified solution I and the modified solution II through a three-fluid nozzle to obtain zirconium oxide silicon oxide nanoclusters, wherein the three-fluid nozzle is provided with two dispersion liquid flow channels and the modified solution I and the modified solution II flow into the nozzle through the two dispersion liquid flow channels respectively, and the particle size distribution of the zirconium oxide silicon oxide nanoclusters is 0.05-500 μm; (3) mixing and stirring the zirconium oxide and silicon oxide nanoclusters, the methacrylate organic matrix and the photoinitiator evenly; (4) The mixture obtained in step (3) is subjected to light curing treatment to obtain a deeply curable zirconium oxide-containing dental restoration resin.
2. The method for preparing a deeply curable zirconium oxide-containing dental restorative resin according to claim 1, characterized in that: The mass proportion of zirconium oxide and silicon oxide nanoclusters in the deeply curable zirconium oxide-containing dental restoration resin is 40-85 wt.%.
3. The method for preparing a deeply curable zirconium oxide-containing dental restorative resin according to claim 1, characterized in that: The size of the nanoparticles in the zirconium oxide dispersion and the silicon dioxide dispersion is 1-100 nm; the solid content in the zirconium oxide dispersion and the silicon dioxide dispersion is 5-40 wt.%; The mass ratio of zirconium oxide in the zirconium oxide dispersion to silicon dioxide in the silicon dioxide dispersion is 1:100 to 100:
1.
4. The method for preparing a deeply curable zirconium oxide-containing dental restorative resin according to claim 1, characterized in that: In step (1), the uniform mixing temperature is 20-25°C and the time is 1-3 hours; The double bond-containing silane coupling agent is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane or γ-mercaptopropyltrimethoxysilane, and the mass ratio of the inorganic nanoparticles to the double bond-containing silane coupling agent is 100:1-50; The reaction temperature of the modification reaction is 40-80°C and the reaction time is 1-24 h.
5. The method for preparing a deeply curable zirconium oxide-containing dental restorative resin according to claim 1, characterized in that: The two dispersion flow channels of the three-fluid nozzle are a middle flow channel, through which the fluid is zirconium oxide dispersion, and an outer flow channel, through which the fluid is silicon dioxide dispersion; The spray drying conditions are as follows: the nozzle diameter is 0.5-2.0 μm, the spray flow rate of compressed air is 0.18-0.91 m 3 / min, the flow rate of the dispersion is 2.5~26.4 mL / min, and the drying temperature is 100~230℃.
6. The method for preparing a deeply curable zirconium oxide-containing dental restorative resin according to claim 1, characterized in that: In step (3), the methacrylate organic matrix is a mixture of bisphenol-A-dimethacrylate glycidyl ester and triethylene glycol dimethacrylate, and the mass ratio of bisphenol-A-dimethacrylate glycidyl ester to triethylene glycol dimethacrylate is 5-7:3-5; The photoinitiator is selected from one or more of 4-N,N-dimethylaminobenzoic acid ethyl ester, 4-(dimethylamino)benzoic acid ethyl ester, N,N-dimethylamino ethyl methacrylate, 2-ethyl dimethyl benzoate, N,N-dimethyl-p-toluidine, N-phenylglycine, diphenylphosphine oxide, 1-phenyl-1,2-propanedione, diphenyliodonium hexafluorophosphate, camphorquinone and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and the amount of the photoinitiator is 0.1-5wt.% of the methacrylate organic matrix; The mixing and stirring is carried out by using a rotating and revolving mixer and a three-roll mill; The rotation speed of the rotary mixer is 600-3000 rpm, and the processing time is 3-10 min; The three-roll mill has an inlet roller spacing of 10-100 μm, an outlet roller spacing of 5-50 μm, and a rotation speed of 10-100 rpm.
7. The method for preparing a deeply curable zirconium oxide-containing dental restorative resin according to claim 1, characterized in that: In step (4), the light curing is blue light curing, the wavelength of the blue light is 430-490 nm, and the power is 1200 mW / cm 2 The light curing time is 20~180 s.
8. A deeply curable zirconium oxide-containing dental restoration resin, characterized in that: The invention discloses a novel novel nanostructured carbon foam. The nanostructured carbon foam is prepared by the preparation method according to any one of claims 1 to 7.
9. A deeply curable zirconium oxide-containing dental restorative resin according to claim 8, characterized in that: The deeply curable zirconium oxide-containing dental restoration resin has an X-ray blocking index of 1 mm to 3 mm, a hardness of 50 to 90 HV, and a curing depth of 1.8 mm to 3.0 mm.
10. The deeply curable zirconium oxide-containing dental restorative resin according to claim 8, characterized in that: The deeply curable zirconium oxide-containing dental restoration resin has a bending strength of 110-180 MPa, a bending modulus of 10-20 GPa, and a compressive strength of 400-450 MPa.
Citation Information
Patent Citations
Machinable resin-infiltrated glass-ceramic materials for dental restoration and their preparation methods
CN107903557B
SOFCs anode slurry and preparation method thereof
CN117239197A
A method for preparing a low-brittle dental crown composite material
CN117598800B
Cited By
Dental resin-based ceramic composite material and preparation method thereof
CN120549779A